PENGARUH MEDIA PEMBELAJARAN GIMKIT TERHADAP HASIL BELAJAR MATEMATIKA MATERI BANGUN DATAR DI KELAS IV SD NEGERI 1 NAIONI - Elisabet Ega; Yulsy M. Nitte; Rosindra Yakoba Nabut; Jeremie Robo Djawa (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
Mathematics learning in elementary schools is often considered difficult and less interesting by students, especially in understanding basic concepts such as plane figures. This has an impact on low learning outcomes due to lack of motivation and active participation in the learning process. This study aims to determine the effect of using gimkit learning media on students’ Mathematics learning outcomes in the material “Recognizing plane figures” at SD Naioni. The method used is quantitative research with a quasi-experimental design of the on- group pretest-posttest design type.the subjects of the study were one class that was given treatment in the form of learning using Gimkit Media.The results of the study showed an increase in student learning outcomes after using Gimkit media.This proves that Gimkit can be an effective learning media in helping student learning outcomes after using gimkit media. This proves that Gimkit can be aneffective learning media helping students understand plane figure material in a more enjoyable and meaningful way